Simulation of the Tanjung Kupang Air Crash - Muhamad, Sallehuddin (2006)
The air crash at Tanjung Kupang, Johor on the 4th December 1977 was the first air accident for the Malaysia Airlines (MAS) and the worst for Malaysia. A Boeing 737-200 with 100 passengers and crews was hijacked before it crashed. Evidences from the accident pointed to an interference of hijackers to the aircraft flight operation. Simulating the accident helped investigators to understand the probable cause of the accident. The Trajectory Reconstruction Method was used to obtain necessary data for the accident simulation. Result from the simulation indicated that the ill-fated aircraft experienced three steep pitch-down pitch-up movements before it stalled and crashed.